2015
DOI: 10.1007/s11121-015-0593-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher Childhood Peer Reports of Social Preference Mediates the Impact of the Good Behavior Game on Suicide Attempt

Abstract: The Good Behavior Game (GBG) is a universal classroom-based preventive intervention directed at reducing early aggressive, disruptive behavior and improving children's social adaptation into the classroom. GBG is one of the few universal preventive interventions delivered in early elementary school that has been shown to reduce the risk for future suicide attempts. This paper addresses one potential mechanism by which the GBG lowers the risk of later suicide attempt. In this study we tested whether the GBG, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 45 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Future studies should aim to identify and test the role of putative environmental factors in the association between impulsive‐aggression and suicidality, as they might be promising targets for early preventive interventions. For example, the Good Behavior Game, an intervention designed to reduce aggression, was found to reduce suicidal behaviors via environmental mechanisms such as improving social adaptation into the classroom (Newcomer et al, ). Understanding the role of such early interventions in reducing environmental risks for impulsive‐aggressive and suicidality may open important clinical avenues.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should aim to identify and test the role of putative environmental factors in the association between impulsive‐aggression and suicidality, as they might be promising targets for early preventive interventions. For example, the Good Behavior Game, an intervention designed to reduce aggression, was found to reduce suicidal behaviors via environmental mechanisms such as improving social adaptation into the classroom (Newcomer et al, ). Understanding the role of such early interventions in reducing environmental risks for impulsive‐aggressive and suicidality may open important clinical avenues.…”
Section: Discussionmentioning
confidence: 99%
“…Muehlenkamp et al (2010) have applied this model to preventing NSSI in predominantly White adolescents through engagement of school personnel as well as peers. Similarly, Newcomer et al (2016) examined the potential mechanisms by which the Good Behavior Game, a classroom-based universal preventive intervention designed to impart self-regulations skills, impacted future risk for suicide attempt. In a majority African American sample, the authors found that social integration and acceptance during first grade may contribute to decreased risk for future suicide attempt.…”
Section: Future Directionsmentioning
confidence: 99%
“…27 The effects on suicidal outcomes were strongest among aggressive males, in whom program effects were mediated by improvements in positive peer ratings for these youth. 28 Hence, the GBG appears to have long-lasting effects on youths' suicidal ideation and behavior, but only if teachers receive the requisite training and supervision.…”
Section: School-based Programsmentioning
confidence: 99%